Brotherhood of kings : how international relations shaped the ancient Near East - Podany, Amanda H. (Oxford University Press, 2010)
"Amanda Podany here takes readers on a vivid tour through a thousand years of ancient Near Eastern history, from 2300 to 1300 BCE, paying particular attention to the lively interactions that took place between the great kings of the day. Allowing them to speak in their own words, Podany reveals how these Near Eastern leaders and their ambassadors devised a remarkably sophisticated system of diplomacy and of trade that extended from the Aegean Sea to Afghanistan, and from the Baltic to central Africa. The allied kings referred to one another as "brothers," kings with equal power and influence who were tied to one another through peace treaties and powerful obligations. They were also often bound together as in-laws, as a result of marrying one another's daughters. These rulers had almost never met one another in person, but they felt a strong connection--a real brotherhood--which gradually made wars between them less common. A remarkable account of a pivotal moment in world history--the establishment of international diplomacy thousands of years before the United Nations--Brotherhood of kings offers a vibrantly written history of the region often known as the cradle of civilization"--Provided by publisher.